Pengaruh Pengolahan Tanah Dan Dosis Pupuk Kandang Ayam Terhadap Pertumbuhan Dan Produksi Tanaman Kacang Hijau (Vigna radiata L.) Di Tanah Inceptisols Ternate - Riswandi Saputra; Adnan Sofyan; Idris Abd Rachman (Universitas Khairun, 2022)
ABSTRACTMung bean (Vigna radiata L.) is a seasonal food crop Â in the form of a shrub that grows upright. The research objective was to determine the effect Â soil processing and dosing of chicken manure and interaction with Â growth and production of green beans. This study used a factorial randomized block design (RBD) with two factors, where the first factor was soil processing P1 = without tillage, P2 = intensive tillage and the second factor was the dose of chicken manure, K0 = control (without fertilizer), K1 = 20 tonnes / ha, K2 = 40 tonnes / ha. The data analysis technique uses ANOVA (Analysis Of Variants), if there is a real effect of the treatment then it is continued with the DMRT Î± 5% test. The results showed that soil treatment had a significant effect on final volume weight, final density, final field capacity, final porosity and plant height at 20 HST, and the number of leaves aged 30 HST, while the combination treatment of soil treatment and chicken manure dose had no significant effect. on plant height growth at 10 HST, 30 HST, the number of leaves at 10 HST. The results showed that the highest dry seed production was 1.78 tons / ha in the P1K1 and P2K2 treatments and the lowest was 1.39 tons / ha in the P2K1 treatment.Keywords: Soil processing, chicken manure, physical properties, green beans, incepstisols